Association between HLA-Cw6 allele expression and characteristics of Javanese ethnic psoriasis patients in Indonesia (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Psoriasis is an autoimmune disease with involvement of genetic and environmental factors. The HLA-Cw6 allele is the strongest genetic factor that correlates with earlier onset and more severe clinical manifestation of psoriasis. In Javanese ethnic, HLA-Cw6 allelic expression has not been identified, although increasing psoriasis patients were found in hospital dermatology departments. The study was aimed to determine the allelic expression of HLA-Cw6 based on the onset and severity of psoriasis in Javanese ethnic. METHODS A cross-sectional study was conducted from March to September 2018. Sixty psoriasis patients in the Margono Soekarjo Hospital and Banyumas Regional General Hospital were recruited consecutively. Psoriasis type, diagnosis, onset, and disease severity were assessed by dermatologists. HLA-Cw6 allelic expression was identified by DNA isolation, quantitative testing, and HLA-Cw6 genotyping. Fisherâs exact and chi-square tests were used to evaluate the association of HLA-Cw6 with age, clinical type, disease severity, onset, and gender. RESULTS The HLA-Cw6 allele positivity was identified at 297 base pairs (bp), while control showed at 618 bp bands. Among 60 subjects, 13 subjects (22%) showed HLACw6 positivity, and 47 subjects (78%) were HLA-Cw6 negative. HLA-Cw6 genotypes were similarly distributed concerning age, onset, gender, clinical type, and disease severity in psoriasis patients of Javanese ethnic (p > 0.05). CONCLUSIONS HLA-Cw6 expression type may not have influence to the characteristics of patients with psoriasis.